A tri-band filter with controllable frequency and transmission zeros using dual-stubs loaded resonators. Issue 2 (17th February 2021) - Lin, Yuanmo; Weng, Min-Hang; Zhang, Ping; Yang, Ru-Yuan
ABSTRACT: This paper presents a high band selectivity tri-band bandpass filter with controllable frequency and transmission zeros. This tri-band bandpass filter is mainly constructed by using two pairs of dual-stubs loaded resonators in a symmetrical structure. Three passbands could be independently controlled to achieve the desired frequency and have transmission zeros created close to the passbands to improve the band selectivity. Three resonant models are provided in the proposed filter to obtain different passband frequencies. The passbands of the designed filter are designed at 1.82, 2.44, and 3.49 GHz, which can be used for global system for mobile communications (GSM), wireless local area network (WLAN), and Worldwide Interoperability for Microwave Access (WiMAX), respectively. The simulated results and measured results of the designed tri-band bandpass filter have a good agreement.